Solar Drying of Agricultural Products I. Drying of Chillies in a Solar Cabinet Dryer - Garg, H P; Krishnan, A (Annals of Arid Zone, 2016)
This paper reports the design details of a simple solar cabinet dryer developed at the Central Arid Zone Research Institute, Jodhpur. The dryer is based on the principle of hot box and is suitable for drying small agricultural . produces like Â«billies, copra, peas, tobacco, etc. The basal area of the dryer is 1.37 sq.m. and its volume is 0.324 Cu.m. The solar cabinet dryer was used for drying Chillies in winter season having initial moisture content 91, 79 to 85 per cent on wet weight basis. In the dryer the average air temperature exceeded 22-8Â°C above the day time average temperature when chillies were kept inside. Field' (tests indicate that by the use of solar dryer the drying time for chillies can be reduced to nearly half of the open drying method. The quality of the chilli es dried by the solar dryer was. also superior. This result is useful since our country has areas under chillies to the tune of 5.8 lakh hectares and this cash crop is also being exported-